Salvadora persica L.: Toothbrush tree with health benefits and industrial applications – An updated evidence-based review - Mohamed Farag; Wael M. Abdel-Mageed; Ali A. El Gamal; Omar A. Basudan (Saudi Pharmaceutical Journal, 2021)
Salvadora persica L. is also known as Arak (in Arabic) and Peelu (in Urdu). Its frequent use as a toothbrush (miswak) is highly recommended by Prophet Muhammad. With a long history in folk medicine for centuries, S. persica was used in oral hygiene, food, cosmetics, fuel, and even as a medicine. Previous phytochemical investigation of its different parts afforded different classes of secondary metabolites such as flavonoids, glycosides, sterols, terpenes, carbohydrates and alkaloids. Organic sulfur-containing compounds and elemental sulfur are also present. In addition, there is a huge research on its biological potentials and industrial applications. Many pharmacological activities were reported experimentally, including antimicrobial, antioxidant, analgesic, anthelmintic, anti-inflammatory, antiulcer, sedative, anticonvulsant, anti-osteoporosis, antidiabetic, hypo-lipidemic, in addition to wound-healing, antidepressant and antitumor activities. Recently, a possible activity against COVID-19 protease was documented by molecular docking. This review tries to provide a recent detailed documentation of folk and modern uses of S. persica, focusing on the possible relations between its chemical constituents, pharmacological properties, and industrial applications. Moreover, a brief about recent analytical and validation methods for the major antimicrobial component is reported.